The Pipeline of Therapeutics Testing During the Emergency Phase of the COVID-19 Outbreak - Canevelli, Marco; Remoli, Giulia; Trentin, Federica; Riccardi, Gabriele; Tariciotti, Leonardo; Risoleo, Giovanni; Ancidoni, Antonio; Bruno, Giuseppe; Cesari, Matteo; Vanacore, Nicola; Raparelli, Valeria (Frontiers in Medicine, 2020)
The coronavirus disease 19 (COVID-19) pandemic is posing a serious threat for the sustainability of healthcare systems and is deeply affecting living conditions worldwide. No therapeutic agent has yet been proven to be effective for the treatment of COVID-19. Its management currently relies on supportive care and the off-label and compassionate use of antivirals and immunomodulators. Nevertheless, a great research effort is in place worldwide to test the efficacy and safety/tolerability profiles of numerous candidate agents that may positively affect the various clinical syndromes associated with COVID-19. In parallel, vaccination and chemoprophylaxis strategies are investigated. The present article provides a summary of the interventional studies targeting COVID-19 in the emergency phase of the outbreak with the aim of broadly informing clinicians and researchers on what happened and what they can expect in the upcoming months. The clinicaltrials.gov database and the European Union (EU) Clinical Trials Register were investigated on March 31, 2020 to identify all the ongoing phase 1-4 research protocols testing pharmacological interventions targeting SARS-CoV-2 infection and/or clinical syndromes associated with COVID-19. Overall, six phase 1, four phase 1-2, 14 phase 2, ten phase 2-3, 19 phase 3, and nine phase 4 studies were identified. Their features are described in the present review. We also provided an updated overview of the change overtime in the pipeline following the emergency phase and based on the current epidemiology of the COVID-19 pandemic.